HOW CAN THE WORLD OVERLOOK Sapindus rarak BIOPROSPECTION? A NICHE FOR INDONESIA - Risha Amilia Pratiwi; Musyarofah Zuhri; Indah Oktaviani (SEAMEO BIOTROP, 2024)
Sapindus rarak is a plant native to Indonesia. Its fruit contains abundant saponins and serves as a detergent for washing batik and baby cloth diapers. This study aims to determine the trends in the S. rarak research based on a bibliometrics and scoping review. The bibliometrics analysis was conducted by defining the search keywords, extracting publications, refining the results, compiling metadata, and mapping authors, keywords, and collaboration. There were 32 publications regarding S. rarak based on Scopus, written by 23 authors between 1992 and 2022, with 387 citations, and 201 publications with 1176 citations due to Google Scholar. Indonesia, the Indonesian Research Institute for Animal Production, and Elizabeth Wina was the most influential country, institution, and author, respectively. The research was clustered to chemistry, biology, medicine, and physics approach. Bio-prospection of S. rarak fruit extract for livestock supplementation was a hot topic. All articles reported S. rarak fruit or seed as the promising organ—no one study about the potency of leaves whereas leaves are also an abundant source of saponin. However, the potency of S. rarak leaves is still overlooked. Research on the efficacy of detergents has not been published in a highly reputable international journal, even though it has been utilized traditionally for a long time. Bibliometrics and scoping review can provide insights for further research roadmaps in this field.